In situ conservation of traditional vegetable diversity in Wa homegardens in southwestern Yunnan, China - Hua Shao; Rosemary Hill; Dayuan Xue; Jingbiao Yang (BMC, 2021)
Abstract Background Homegardens are in situ conservation sources of germplasm diversity for overcoming homogenous germplasm problems in industrial agricultural systems. The Wa people constitute a long-dwelling ethnic group mainly in southwestern Yunnan with a unique culture and rich knowledge of traditional vegetables. We hypothesized that traditional vegetable varieties are well conserved in Wa homegardens because Wa culture promotes the preservation of traditional vegetables. We surveyed vegetable varieties and the practices that are involved in the conservation of traditional vegetables in Wa homegardens, which could form the basis for in situ conservation. Methods The methods were used including questionnaires and semi-structured interviews. Sixty homegardens were surveyed through purposive sampling in 6 Wa villages. We documented ethnobotanical information about vegetables in homegardens. Plant species were identified according to the Flora of China. And thematic analyses were conducted for in-depth interviews to identify the conservation factors for traditional vegetables. Results Fifty-two vegetable species belonging to 16 families and 41 genera were recorded from 60 Wa homegardens. Fifty-five traditional vegetable varieties and thirty-six hybrids were recorded. Among all the villages, 23 ± 6 (average ± SD) traditional vegetable varieties per homegarden and 9 ± 3 (average ± SD) introduced varieties per homegarden were recorded. Local seeds were stored in 78% of households, with an additional 9% of households' seed supplies coming from neighbors and relatives; the other 13% of households purchased local seeds from markets. In 83% of families, the female head was mainly responsible for the decision-making concerning traditional vegetables in homegardens; in 10% of families, the male head was responsible for decision-making, and a small percentage (2%) was determined by elderly people. Five percent of families made decisions jointly between male and female household heads. Conclusions This study demonstrated that rich traditional germplasm diversity is harbored in Wa homegardens because of the unique culture and traditional knowledge of Wa communities, which are practiced daily with homegrown food plants. Local vegetable seed conservation and sharing systems help maintain germplasm diversity in the Wa community homegardens. Wa homegardens constitute a practical solution for protecting traditional germplasm diversity and maintaining traditional lifestyles.